2021
DOI: 10.1038/s41396-021-01046-1
|View full text |Cite
|
Sign up to set email alerts
|

Decline in symbiont-dependent host detoxification metabolism contributes to increased insecticide susceptibility of insects under high temperature

Abstract: The interactions between insects and their bacterial symbionts are shaped by a variety of abiotic factors, including temperature. As global temperatures continue to break high records, a great deal of uncertainty surrounds how agriculturally important insect pests and their symbionts may be affected by elevated temperatures, and its implications for future pest management. In this study, we examine the role of bacterial symbionts in the brown planthopper Nilaparvata lugens response to insecticide (imidacloprid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 64 publications
0
50
0
Order By: Relevance
“…Additionally, the observed seasonal fluctuations in the microbial titers could also be an outcome of changing external temperatures. In fact, a recent study ( Zhang et al., 2021 ) has demonstrated the effect of temperature on BPH-bacterial symbiosis and its consequent impact on host susceptibility to insecticide (imidacloprid).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the observed seasonal fluctuations in the microbial titers could also be an outcome of changing external temperatures. In fact, a recent study ( Zhang et al., 2021 ) has demonstrated the effect of temperature on BPH-bacterial symbiosis and its consequent impact on host susceptibility to insecticide (imidacloprid).…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia sp. in planthoppers [32]). Finally, thermal conditions determine the outcomes of interactions between insect hosts and facultative symbionts acting as reproductive manipulators, notably affecting the incidence of male killing and cytoplasmic incompatibility (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have shown that N. lugens and endosymbionts form a stable mutualistic symbiosis, mutual dependence, and influence relationship due to their irreplaceable functional requirements ( Sapp, 2002 ). Previous studies on endosymbionts of N. lugens mainly focused on diversity and dynamics of microbial communities at different developmental stages or feeding on different resistant rice varieties and their role in mediating host resistance ( Cai et al, 2020 ; Jin et al, 2021 ; Zhang et al, 2021 ). Synergy effect of antimicrobials and insecticides on N. lugens population should be further explored given the close relationship between N. lugens and endosymbionts .…”
Section: Introductionmentioning
confidence: 99%
“…Pymetrozine can be used to control aphids, leafhoppers, Bemisia tabacis , and rice planthoppers due to its high selectivity while showing safety to biological natural enemies of rice planthoppers, such as spiders and Anagrus nilaparvataes , during the control process ( Preetha et al, 2010 ; Lin et al, 2021 ). The resistance of N. lugens to pymetrozine, sulfoxaflflor, nitenpyram, ect chemical insecticides has increased evidently in recent years ( Liao et al, 2019 ; Zhang et al, 2021 ). Some field populations of N. lugens in China still remained susceptible to pymetrozine in 2010, but the resistance increased to medium or high levels in 2011 and 2012 ( Zhang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%